Pedagogical innovation and educator wellbeing in UK audiology teaching: cross-institutional insights from the COVID-19 experience - Chundu, Srikanth; Morley, Natalie; Jansson-Boyd, Cathrine V.; Parmar, Bhavisha (Frontiers in Medicine, 2025)
BackgroundAcademic teaching staff in higher education routinely balance multiple roles, including teaching, research, and pastoral student care. The onset of the COVID-19 pandemic, which forced the closure of university campuses, significantly intensified these demands. To maintain the continuity and quality of education, staff were required to swiftly adapt and implement new, robust teaching methods. This sudden shift placed additional pressure on an already stretched workforce. This study aims to investigate the impact of the COVID-19 pandemic on audiology education in the United Kingdom (UK), with a particular focus on the work-related wellbeing of academic teaching staff.MethodsA qualitative study was conducted using semi-structured interviews with eleven teaching staff involved in audiology higher education across the UK.ResultsThe following four themes were identified (1) initial institutional response to the pandemic, (2) adapting practical audiology training through teleaudiology and patient simulation, (3) supporting students whilst safeguarding staff wellbeing, and (4) pedagogical approaches for a unique, technology-driven audiology profession.ConclusionThe detrimental impact of the pandemic on academic staff well-being was evident in the form of increased workloads and escalating institutional pressures, which frequently prioritized student well-being over that of staff. Audiology HEI educators acknowledged that while audiology training cannot be entirely conducted online due to the essential hands-on skills that must be practiced in person, a hybrid or blended learning approach could be beneficial.